Development and Validation of the Health Competence Beliefs Inventory in Young Adults With and Without a History of Childhood Cancer - DeRosa, Branlyn Werba (2011)
BACKGROUND: Adolescent and young adult survivors of childhood cancer are a vulnerable population. Health beliefs may be related to necessary follow-up care. PURPOSE: This study seeks to develop a measure of health beliefs for adolescents and young adults with and without a history of cancer. METHODS: Inductive and deductive methods and focus groups were used to develop the Health Competence Beliefs Inventory. Cancer survivors (n=138) and comparison participants (n=130) completed the Health Competence Beliefs Inventory and other measures. Healthcare providers reported current medical problems. RESULTS: A series of iterative exploratory factor analyses generated a 21-item four-factor solution: (1) Health Perceptions; (2) Satisfaction with Healthcare; (3) Cognitive Competence; and (4) Autonomy. Survivors reported significantly different Health Competence Beliefs Inventory scale scores than comparisons (p<.05). The Health Competence Beliefs Inventory was associated with beliefs, affect, quality of life, posttraumatic stress symptoms, and medical problems. CONCLUSIONS: The Health Competence Beliefs Inventory is a promising measure of adolescent and young adult perceptions of health and well-being.